Leaf traits variation during leaf expansion in Quercus ilex L. - Gratani, L; Bonito, A (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.
Keywords: leaf anatomy; leaf expansion; leaf morphology; net photosynthetic rate; Quercus ilex